Acceptance and competitiveness of new improved wheat varieties by smallholder farmers. Issue 4 (4th July 2017) - Joshi, Krishna D.; Rehman, Attiq U.; Ullah, Ghullam; Nazir, Mian F.; Zahara, Mahreen; Akhtar, Jamil; Khan, Muhammad; Baloch, Amanullah; Khokhar, Jaleelullah; Ellahi, Ehsan; Khan, Attaullah; Suleman, Muhammad; et al.
ABSTRACT: We conducted this research because earlier research revealed that Pakistani farmers were growing 8–10-year-old wheat (Triticum aestivum L.) varieties and hence not benefitting from the recent advances in wheat breeding. Participatory varietal selection (PVS) trials were conducted to have farmers validate and include newly released wheat varieties into seed-production stream to speed up replacement of old and obsolete wheat varieties by farmer-preferred new high-yielding varieties. Fourteen new varieties recommended for irrigated and eight for rainfed environments were evaluated in this research involving smallholder farmers in food-deficit districts of Pakistan. Collaborating farmers preferred 10 varieties from the PVS trials, eight of which were germplasm from the International Maize and Wheat Improvement Center (CIMMYT) that yielded on average 5–17% more grain than local checks. Local checks used in the PVS trials in Sindh and Khyber Pakhtunkhwa were old improved varieties. Greater yield advantage from new varieties over local checks was reported from rainfed environments and areas where old local checks were used. The PVS research showed the possibility of ensuring food security of smallholder farmers as new high-yielding varieties gave an additional 0.3 –0.5 tons of grain per ha, sufficient to feed two to three persons per year. Research also revealed that innovative farmers in rainfed regions grew wheat varieties recommended for irrigated regions to identify high-yielding wheat varieties with stable performance. Feedback by farmers to wheat breeding research system was to develop even higher yielding new wheat varieties with diseases resistance to replace old and obsolete varieties to boost food security.